2017
DOI: 10.3390/v9010012
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Pathological Phenotype of Bovine Astrovirus CH13/NeuroS1 Infection in Neurologically-Diseased Cattle: Towards Assessment of Causality

Abstract: Next-generation sequencing (NGS) has opened up the possibility of detecting new viruses in unresolved diseases. Recently, astrovirus brain infections have been identified in neurologically diseased humans and animals by NGS, among them bovine astrovirus (BoAstV) CH13/NeuroS1, which has been found in brain tissues of cattle with non-suppurative encephalitis. Only a few studies are available on neurotropic astroviruses and a causal relationship between BoAstV CH13/NeuroS1 infections and neurological disease has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 22 publications
5
52
0
Order By: Relevance
“…To date, nine cases of meningoencephalitis have been attributed to human astroviruses, with astrovirus VA1 (VA1) as the most frequent astrovirus genotype (Brown et al, 2015;Cordey et al, 2016;Fremond et al, 2015;Lum et al, 2016;Naccache et al, 2015;Quan et al, 2010;Sato et al, 2016;Wunderli et al, 2011). In one study of cattle, astroviruses account for 34% of cases of encephalitis that were previously without an identified etiology (Selimovic-Hamza et al, 2017).…”
Section: Commentary Background Informationmentioning
confidence: 99%
“…To date, nine cases of meningoencephalitis have been attributed to human astroviruses, with astrovirus VA1 (VA1) as the most frequent astrovirus genotype (Brown et al, 2015;Cordey et al, 2016;Fremond et al, 2015;Lum et al, 2016;Naccache et al, 2015;Quan et al, 2010;Sato et al, 2016;Wunderli et al, 2011). In one study of cattle, astroviruses account for 34% of cases of encephalitis that were previously without an identified etiology (Selimovic-Hamza et al, 2017).…”
Section: Commentary Background Informationmentioning
confidence: 99%
“…Duck astroviruses have been shown to be associated with duck viral hepatitis (DVH) [25]. Many studies have reported that some AstV strains, such as the human astrovirus MLB and VA strains, bovine astrovirus NeuroS1 strain, PAstV type 3, and mink astrovirus SMS strain, can damage the central nervous system (CNS) and cause encephalitis and meningitis [22,[26][27][28][29], suggesting the potential for the extraintestinal and neuropathology infection processes of astroviruses.…”
Section: Introductionmentioning
confidence: 99%
“…In minks, an astrovirus genotype is the causative agent of shaking mink syndrome, a neurological disorder of minks characterized by tremors and seizures (40,41). Bovine astroviruses have been identified as a significant cause of encephalitis in cattle, as these viruses have been detected in 34% of previously unexplained cases of encephalitis (42)(43)(44)(45)(46)(47). An additional astrovirus genotype has also been identified as a cause of encephalitis in sheep (48).…”
mentioning
confidence: 99%